DISCRETE ANALOGUE OF THE POISSON INTEGRAL FOR A BALL - Khomchenko, A. N.; Motaylo, A. P. (Radio Electronics, Computer Science, Control, 2012)
The Dirichlet problem for the ball with discretely given conditions on the boundary is solved in the work. Construction from hexahedron and octahedron inscribed in a ball is used in the role of computational template. A discrete analogue of the Poisson integral formula in the form of a proportional stratified sampling is obtained.